Pengaruh Ketebalan Bahan Dan Jumlah Desikan Terhadap Laju Pengeringan Jahe (Zingiber Officinale Roscoe) Pada Pengering Kombinasi Surya dan Desikan - Hasibuan, Rosdanelli; Alfikri Ridhatullah, Muhammad (Jurnal Teknik Kimia USU, 2019)
Ginger is a spice plant that is usually used as a seasoning in cooking or raw material for medicine, traditional or industrial medicine. Ginger has a high-water content so its easily contaminated with microbes and has active ingredients (gingerol) which are easily damaged by high temperatures. Ginger drying is intended for maintaining the quality of dry ginger and keep ginger from microbes. The drying process has done in continuously with solar dryer using flat plate type collector during the day and at night using the Molecular Sieve 13x desiccant. Drying varies the thickness of ginger 2 mm, 4 mm, and 6 mm, and the amount ratio of desiccant: 1:1; 1:2; and 1:3. To get drying characteristics, every 1-hour mass calculated using an electric scale, and data logger every 5 minutes calculates the temperature and humidity rate (RH) in the drying chamber. The result from ginger drying is the thickness of 6 mm needed more than 20 hours of drying process so that it needed the combination of dryer compared to other thickness, and from quality analysis results of dry ginger, ash content parameters already accordance with SNI standards, and 1:1 material and desiccant ratio is the variation that most closely matches the SNI standard.